Historicizing Sustainable Livelihoods: A Pathways Approach to Lead Mining in Rural Central China - Lu, J; Lora-Wainwright, A (Elsevier, 2014)
This article adopts a "pathways to sustainability" approach to study lead mining in rural China. Through an in-depth case study, it reveals how shifting mining practices are tied to institutional and political economic contexts, cost-benefit distribution, and changes in livelihood resources and strategies. It weaves together an analysis of livelihood practices with a study of attitudes to livelihood and environment, which are usually researched separately. In turn, it demonstrates that a longitudinal analysis may resolve the contradictory accounts of whether mining aids or hinders development, and whether local communities are victims or beneficiaries of such development.